Implementing and evaluating gender-transformative approaches in agrifood systems: What does the evidence say? - Singh, Sabina; Puskur, Ranjitha (CGIAR GENDER Impact Platform, 2023)
The evidence base for the effectiveness of gender-transformative approaches (GTAs) in agriculture and food system interventions is small and weak, and many studies do not focus on specifically evaluating these approaches and methods. While the very limited quantitative evidence suggests that interventions that integrate GTAs have weak or no effects on many outcomes for women’s empowerment outcomes (including gender norms), qualitative evidence shows that, in some instances, shifts in gender roles could eventually lead to change in gender norms. Changes in norms can take generations, so studies examining different approaches to GTAs, including different intervention durations and intensities, and longer-term studies are needed to better understand the effects of GTAs on households and communities.